Copper Promotes Tumorigenesis by Activating the PDK1‐AKT Oncogenic Pathway in a Copper Transporter 1 Dependent Manner. Issue 18 (18th July 2021) - Guo, Jianping; Cheng, Ji; Zheng, Nana; Zhang, Xiaomei; Dai, Xiaoming; Zhang, Linli; Hu, Changjiang; Wu, Xueji; Jiang, Qiwei; Wu, Depei; Okada, Hitoshi; Pandolfi, Pier Paolo; et al.
Abstract: Copper plays pivotal roles in metabolic homoeostasis, but its potential role in human tumorigenesis is not well defined. Here, it is revealed that copper activates the phosphoinositide 3‐kinase (PI3K)‐protein kinase B (PKB, also termed AKT) oncogenic signaling pathway to facilitate tumorigenesis. Mechanistically, copper binds 3‐phosphoinositide dependent protein kinase 1 (PDK1), in turn promotes PDK1 binding and subsequently activates its downstream substrate AKT to facilitate tumorigenesis. Blocking the copper transporter 1 (CTR1)‐copper axis by either depleting CTR1 or through the use of copper chelators diminishes the AKT signaling and reduces tumorigenesis. In support of an oncogenic role for CTR1, the authors find that CTR1 is abnormally elevated in breast cancer, and is subjected by NEDD4 like E3 ubiquitin protein ligase (Nedd4l)‐mediated negative regulation through ubiquitination and subsequent degradation. Accordingly, Nedd4l displays a tumor suppressive function by suppressing the CTR1‐AKT signaling. Thus, the findings identify a novel regulatory crosstalk between the Nedd4l‐CTR1‐copper axis and the PDK1‐AKT oncogenic signaling, and highlight the therapeutic relevance of targeting the CTR1‐copper node for the treatment of hyperactive AKT‐driven cancers. Abstract : Besides playing pivotal roles in metabolic homoeostasis, copper also binds PDK1 to activate its downstream AKT kinase, which in turn facilitates tumorigenesis. Meanwhile, the copper transporter 1 (CTR1) is negatively regulated by Nedd4l‐mediated ubiquitination and subsequent degradation, indicating a novel regulatory crosstalk between the Nedd4l‐CTR1‐copper axis and the PDK1‐AKT oncogenic signaling to govern tumorigenesis.